SYSTEMS OF COMPANY’S FINANCIAL CRISIS DIAGNOSTICS - Klodāne, Aļona; Mietule, Iveta; Beinaroviča – Litvinova, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
At present, a company's crisis management becomes an urgent issue worldwide, while in Latvia crisis diagnostics and management have not been sufficiently studied thus far. A financial crisis expanding in the company causes significant problems to the company's economic and growth processes, and can turn into a bankruptcy, when the only solution would be the company's liquidation. Instead, early detection of crisis significantly increases the possibilities of solving the company's financial crisis, saving assets and future development opportunities. The aim of the research is to carry out a comparative analysis of basic financial crisis diagnostic systems, revealing their essential substance and possibilities of application. To achieve the aim of the research, a range of methods – monographic, comparative and content-analysis, grouping and graphical methods – were used. In the result of the research, the authors have come to the conclusion that, in the case a practical necessity for timely diagnosis of signs of a company’s financial crisis exists, the theory offers two basic systems differing by their general objectives and implementation methods.